Nanoscale evolution of interface morphology during electrodeposition - Nicholas M. Schneider (Nature Portfolio, 2017)
Understanding structure evolution during electrochemical growth is crucial in materials processing and design of devices such as batteries. Here, the authors image copper during electrodeposition to provide strategies for controlling interface morphology.